2008
DOI: 10.1002/marc.200700844
|View full text |Cite
|
Sign up to set email alerts
|

Novel Electrospun Nanofibers Composed of Polyelectrolyte Complexes

Abstract: A simple method to obtain novel nanofibers composed of polyelectrolyte complexes (PECs) has been proposed. It consists of the electrospinning of a mixed homogeneous solution of polyelectrolyte partners, and the formation of PEC during the electrospinning. This was achieved by careful choice of the composition of the spinning solutions. Chitosan was the polycationic partner, with either a weak polyacid [poly(acrylic acid), PAA] as a counterpart or a strong one [poly(2‐acrylamido‐2‐methylpropanesulfonic acid), P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 24 publications
2
32
0
Order By: Relevance
“…In our previous studies we have shown that for preparation of PEC nanofibers from chitosan and strong polyacid the addition of a low-molecular-weight salt is required. 15 In the present study, when the strong polyacid PAMPS is used as a partner in the PEC TMCh/PAMPS for the preparation of a homogeneous common spinning solution the use of a 85 wt.% HCOOH solvent system and the addition of a low molecular weight salt (1.5 wt. % CaCl 2 ) were found to be appropriate.…”
Section: Preparation and Characterization Of Electrospun Nanofibers Bmentioning
confidence: 99%
“…In our previous studies we have shown that for preparation of PEC nanofibers from chitosan and strong polyacid the addition of a low-molecular-weight salt is required. 15 In the present study, when the strong polyacid PAMPS is used as a partner in the PEC TMCh/PAMPS for the preparation of a homogeneous common spinning solution the use of a 85 wt.% HCOOH solvent system and the addition of a low molecular weight salt (1.5 wt. % CaCl 2 ) were found to be appropriate.…”
Section: Preparation and Characterization Of Electrospun Nanofibers Bmentioning
confidence: 99%
“…PECs are a type of composite fiber produced by mixing two polymers with opposite charges stabilized by strong electrostatic interactions between the polycation and polyanion. [ 7 , 14 , 15 , 16 , 17 , 18 ]. The materials based on PECs are often characterized by a degree of swelling depending on pH and external ionic concentration [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…To stabilize fibrous hydrogels in aqueous media, thermal or vapor‐phase crosslinking is required which impedes their applications. Polyelectrolyte complexes have been used to improve the stability of fibrous hydrogels in aqueous solutions . A polyelectrolyte complex is formed by mixing oppositely charged polyelectrolytes such as poly(acrylic acid) (PAA) and poly(allyl amine hydrochloric acid) or PAA and chitosan (CS) in solutions with controlled polymer ratio and pH.…”
Section: Introductionmentioning
confidence: 99%
“…A polyelectrolyte complex is formed by mixing oppositely charged polyelectrolytes such as poly(acrylic acid) (PAA) and poly(allyl amine hydrochloric acid) or PAA and chitosan (CS) in solutions with controlled polymer ratio and pH. The electrostatic interactions between partially charged polymeric chains lead to the formation of a polymer hydrogel network without covalent crosslinkers . However, when exposed to solutions with high salt concentration and extreme pH, the disruption of the electrostatic interactions between polycations and polyanions results in the dissolution of the fibers.…”
Section: Introductionmentioning
confidence: 99%